Students' Learning Obstacles in Exponential: A Case Study in Indonesian Higher Education Students - Suarka, Ni Komang Savitri Dharma; Kusumah, Yaya Sukjaya (FKIP Universitas Lampung, 2024)
Exponential is an essential concept in mathematics learning. Students generally understand the idea of exponentials if the base and power are natural numbers. However, when the base and the power are a negative integer, students experience difficulties, which can create learning obstacles. This research aims to identify and analyze learning obstacles that confront students at the stage of solving exponent problems, especially in the exponent form〖 -(a)〗^(-b),∀a∈Ν,b∈Z. This study uses a qualitative method with a case study type. The participants of this study were nine higher education students in Bandung. Subjects are asked to take a written test of seven questions to explore their understanding of exponents with specific characteristics. The results of the research showed that all of the learning obstacles that arise are epistemological learning obstacles, Including errors in defining exponents when the power is zero, when the power is a negative integer, when the base contains a negative sign, when the base contains a negative sign and the power is zero, and when the base contains a negative sign with a negative integer exponent. The research results obtained can be used to develop a hypothetical learning trajectory. Keywords: learning obstacle, exponential, epistemological learning obstacle, negative exponential.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp530-541